Reducing the physical, social, and emotional impact of episodic migraine: Results from erenumab STRIVE and ARISE phase III randomized trials. Issue 2 (8th February 2022) - Kawata, Ariane K.; Ladd, Mary Kate; Lipton, Richard B.; Buse, Dawn C.; Bensink, Mark; Shah, Shweta; Hareendran, Asha; Mannix, Sally; Mikol, Daniel
Abstract: Objective: The purpose of this study was to examine changes in the functional impact of migraine following treatment with erenumab, as measured by the Migraine Functional Impact Questionnaire (MFIQ). Background: The MFIQ, a novel patient‐reported outcome (PRO) measuring the impact of migraine on four domains (physical function, social function, and emotional function [PF, SF, and EF]; usual activities [UAs]) and a single item assessing overall impact on UA, was included in phase III trials evaluating erenumab 70 and 140 mg monthly for migraine prevention among people with episodic migraine (EM). Methods: In the ARISE study, 577 patients with EM were randomized to erenumab 70 mg or placebo. In the STRIVE study, 955 patients with EM were randomized to erenumab, 70 mg or 140 mg or placebo. Pairwise comparisons of least‐squares mean (LSM) change from baseline in MFIQ scores (with associated 95% confidence interval [CI]) were assessed for each active treatment versus placebo. Results: In ARISE, greater reductions from baseline to month 3 were observed for 70 mg versus placebo for PF (LSM [95% CI]: −3.2 [−6.4 to −0.1]; p  = 0.046) and EF (−4.0 [−7.3 to −0.7]; p  = 0.019) domain scores. In STRIVE, between‐group differences also reflected reductions from baseline to the average of months 4–6 that favored erenumab on all four MFIQ domain scores. Reductions in impact for 70 mg compared to placebo were −4.3 (95% CI: −6.8 to −1.7; p  < 0.001) for PF, −4.0 (−6.3 to −1.7; p  < 0.001) for UA, −3.7 (−6.1 to −1.2; p  = 0.003) for SF, and −5.3 (−7.9 to −2.6; p  < 0.001) for EF domain scores. Improvements were also observed for 140 mg versus placebo with between‐group differences of −5.7 (95% CI: −8.2 to −3.2; p  < 0.001) in PF, −5.1 (−7.5 to −2.8; p  < 0.001) in UA, −5.0 (−7.4 to −2.6; p  < 0.001) in SF, and −7.2 (−9.9 to −4.5; p  < 0.001) in EF domain scores. There were also greater improvements in the overall impact on UA score for 70 mg (LSM [95% CI]: −4.3 [−7.0 to −1.7]; p  = 0.001) and 140 mg (−5.3 [−8.5 to −3.2]; p  < 0.001) versus placebo. Conclusions: The MFIQ measures the frequency of impacts and level of difficulty on multiple functional domains that provide a more complete picture of the effects of migraine. MFIQ scores showed that in comparison with placebo, patients treated with erenumab had greater reductions in the functional impact of migraine, providing insight into treatment benefits that extend beyond improvements in clinical status and health‐related quality of life previously reported based on clinical end points and other PROs.